Recommendations for the analysis of hemocyte-related immunocompetent oxidative activity in the freshwater snail Lymnaea stagnalis - P. Boisseaux; P. Noury; M.-L. Deli; H. Thomas; J. Garric (MDPI AG, 2016)
Not available